Efficiency of Packaging Design as a Marketing Tool: A Case Study Of Elite Bakery Limited Kabale Branch. - Muhweezi, Moses (Kabale University, 2023)
The study was carried out regarding the efficiency of packaging design as a marketing tool of roducts. A study of Elite Bakery Limited, was guided by the following objectives; to identify the forms of packaging used by Elite Bakery limited in promoting their sales, to examine the role played by packaging design towards the marketing of their product, to identify the challenges faced in the design of packaging their products with aim of improving :.::eir sales momentum and to find the relationship between packaging design and marketing c the Baking Industry. The researcher used descriptive, cross-sectional and explanatory research designs. Data was collected using questionnaires, interview guide. Data was collected from two sources; primary and secondary source using a sample size of 50 respondents. :: was discovered that Elite Bakery Company widely used various forms of packaging for which they received well over 100% respondents. Whereby they had various types of packages including; plastic, plastic paunches, plastics bottles, Automatic pouch making, Elite bakery filling & pouch sealing machines with a printing provision. The findings of the study concluded that apart from the packaging which affects the market volume, but there are other factors such as research and development, good customer care, price reduction, good after sales service and wide coverage which also influence consumption behavior of customers in the market. The researcher recommended that Elite bakery needed to develop a profound packaging design that will suit the marketing of their products with the focus to identify which media to use while communicating to their consumers. It is paramount to put emphasize in planning promotional programs and goals whereas set out strategies aimed at ensuring proper evaluations, control of packaging and make adjustments where possible.